Dutch reference values for the Patient-Reported Outcomes Measurement Information System Scale v1.2 - Global Health (PROMIS-GH) - Ellen B. M. Elsman; Leo D. Roorda; Martine H. P. Crins; Maarten Boers; Caroline B. Terwee (SpringerOpen, 2021)
Abstract Background To add context to the impact of medical conditions, it is important to interpret and compare health outcomes across studies and populations. We aimed to determine Dutch reference values for the Patient-Reported Outcomes Measurement Information System Scale v1.2 - Global Health (PROMIS-GH). Methods The PROMIS-GH, also referred to as PROMIS-10, was completed by 4370 Dutch persons, representative for the 2016 Dutch population. T-scores for the mental health (GMH) and physical health (GPH) subscales, and their shorter two-item subscales, were calculated for the entire population, age groups and gender. T-scores for GMH and GPH were compared to the US reference population, representative for the 2000 US general population. Interpretability thresholds for poor, fair, good, very good and excellent GPH and GMH were calculated based on T-scores of participants, which were categorized into five groups based on their response to item Global01. For each group the mean GPH and GMH T-score was calculated and the midpoint between two adjacent means was identified, resulting in thresholds. Thresholds based on the Dutch data were compared to US thresholds. Results The Dutch population had a GMH T-score of 44.7 and a GPH T-score of 45.2, both substantially worse than the US reference population T-score of 50. Lower T-scores were also found for age-range and gender subpopulations. Dutch GMH and GPH interpretability thresholds were mostly not substantially different compared to the US thresholds, although the Dutch threshold between fair and poor mental health was considerably higher (29 vs. 38). Conclusions This study reports reference values for the PROMIS-GH scale for the Dutch general population, including age-range and gender subpopulations. These reference values provide an important tool for healthcare professionals and researchers to better evaluate and interpret patient-reported mental health and physical health. Scores are notably worse than the US reference values. The exact reason for this remains subject for further research, although possibilities for the differences are discussed, including the presence of differential item functioning and the representativeness and recentness of the data.